(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Today the new challenges in the world assign a key role to the distance online education in the formation of knowledge and competencies. The development of Internet technologies provides opportunities for much better distance online education. The use of various digital platforms increases the efficiency and improves the way of delivering information to the students. Different types of multimedia applications improve the perception of the learning material. The subject of this report is the development of a methodology for distance online training of welding specialists at the Institute of Metal Science, Equipment and Technologies with Hydro- and Aerodynamics Centre "Acad. A. Balevski" at BAS.